2018
DOI: 10.31983/jrg.v6i2.4298
|View full text |Cite
|
Sign up to set email alerts
|

Efektifitas Pemberian Buah Apel Manalagi Dengan Dosis Bervariasi Terhadap Penurunan Kadar Glukosa Darah Pada Penderita Diabetes Mellitus Tipe Ii Di Kelompok Prolanis Puskesmas Genuk Kota Semarang

Abstract: Background :Diabetes mellitus is a carbohydrate metabolism disorder characterized by an increased in blood glucose levels due to abnormal / decreased insulin work. Diet for people with diabetes mellitus is a food with a balanced composition between carbohydrates, protein, fat and fiber. Water soluble fiber namely pectin in apples is able to slowing the entry of glucose in the body. Objective : To know the effectiveness of giving apple manalagi with varying dose to decrease blood glucose level in type II diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
1
0
0
2
Order By: Relevance
“…The level of energy, carbohydrate, fiber, and vitamin C intakes did not statistically have a significant effect on changes in blood glucose levels. The results of this research are in line with that of Ayuhapsari et al (2018) where they found that energy, carbohydrate, and fiber intakes did not affect changes in fasting blood glucose 6 .…”
Section: Discussionsupporting
confidence: 89%
“…The level of energy, carbohydrate, fiber, and vitamin C intakes did not statistically have a significant effect on changes in blood glucose levels. The results of this research are in line with that of Ayuhapsari et al (2018) where they found that energy, carbohydrate, and fiber intakes did not affect changes in fasting blood glucose 6 .…”
Section: Discussionsupporting
confidence: 89%
“…Buah naga (hylocereus) merupakan salah satu buah yang dapat digunakan sebagai terapi jus karena tinggi serat, kalsium, magnesium, potasium dan sodium (Astuti, 2019). Apel manalagi misalnya dengan pemberian 2 x 200 gram yang mengandung 9,6 gram (38,4%) serat pektin menurunkan kadar glukosa darah puasa subjek penelitian rata-rata 150,16 mg/dl (Ayuhapsari et al, 2018).…”
Section: Tabel 2 Rata-rata Asupan Zat Gizi Subjek Sebelum Dan Setelah...unclassified
“…Pemberian apel tiga kali seminggu selama tujuh hari dapat menurunkan kadar glukosa darah pada pasien diabetes melitus hingga 45 mg/dl. Selanjutnya, makan 100 gram apel dua kali sehari dapat menurunkan kadar glukosa darah pada penderita diabetes baru dalam 15-30 hari dan pada penderita diabetes kronis dalam 3-4 bulan (Ayuhapsari et al, 2018).…”
Section: Pengaruh Pemberian Jus Buah Naga Apel Dan Pepayaunclassified